Gut microbiota and sepsis and sepsis-related death: a Mendelian randomization investigation - Shang, Weifeng; Zhang, Sheng; Qian, Hang; Huang, Sisi; Li, Hui; Liu, Jiao; Chen, Dechang (Frontiers in Immunology, 2024)
It is unclear what the causal relationship is between the gut microbiota and sepsis. Therefore, we employed MR to determine whether a causal link exists between the two.Methods: This study used publicly available GWAS summary data of gut microbiota, sepsis, sepsis (critical care), and sepsis (28-day death in critical care) to perform a two-sample MR analysis. To ensure the robustness of the results, we also conducted a sensitivity analysis.Results: For sepsis susceptibility, IVW estimates revealed Victivallales (OR= 0.86, 95%CI, 0.78-0.94, P = 0.0017) was protective against sepsis.While, Lentisphaerae (OR=0.89, 95% CI, 0.80-0.99),